Deixis Analysis of The Character Wednesday Addams: Wednesday Series First Season - Nufus, Kholishotin; Andayani, Endah Alamsari; Prasetyo, Yudy (Journal of English Development, 2026)
This study investigates the use of deixis in the character of Wednesday Addams in the Netflix series Wednesday Season 1 (2022) from a pragmatic perspective. Deixis plays a crucial role in shaping meaning, character identity, and interaction within audiovisual discourse. The objective of this research is to identify the types of deixis used by Wednesday Addams and to explain how deixis reflects her personality and interpersonal relationships. This study employed a descriptive qualitative method with content analysis as the research design. The data were collected from Wednesday Addams’ utterances across all episodes and analyzed using Yule’s (1996) theory of deixis, covering personal, spatial, and temporal deixis, and Miles and Huberman’s (1994) model of qualitative data analysis. The results show that personal deixis is the most dominant type with 624 occurrences, followed by temporal deixis with 139 occurrences and spatial deixis with 124 occurrences. The findings indicate that deixis significantly reflects Wednesday’s independent, emotionally detached, and dominant personality in social interactions. In conclusion, deixis functions not only as a linguistic device but also as an essential tool in constructing character identity and narrative meaning in audiovisual media.